The Influence of Sharia Marketing and Product Literacy on Public Interest in Making Transactions at Islamic Banks (Case Study of Indonesian Islamic Bank Customers) - Ibrahim, Fadel Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Islamic banking is one of the instruments seen in determining the development of Islamic economics in Indonesia. Along with the development of Islamic banking, of course, it must continue to strive to strengthen public confidence to continue using Islamic bank products. This study aims to examine the variables of Sharia marketing and product literacy on public interest in using Indonesian Islamic bank products, in the city of Medan. This research uses a quantitative research approach, with the SmartPLS analysis tool.3. The results obtained show that there is no significant influence between Sharia marketing variables on public interest in making transactions at Indonesian Islamic banks. While the product literacy variable has an influence on public interest in making transactions in Islamic banks. The effect is 7.581%, and the model obtained is ????1 = 0,874 ????1 + 7,581 ????2 + ????. Further research can use other models or add moderating or intervening variables in conducting research, in order to find out which is an obstacle in conducting transactions at Islamic banks.